Practice and Research on the Teaching Strategy of "Semi-finished Product Processing" Oriented to Knowledge System Construction - Xiulin, Ma; Xiaomin, Zhang; Sheng, Li; Chenyu, Fan (Advances in Social Sciences Research Journal, 2020)
The development of education informatization has led to the innovation of the teaching mode and learning mode. In this process, the teaching mode based on the knowledge system has become the main direction of the reform of the teaching model in the information age. The "semi-finished product processing" as a teaching strategy which helps learners promote knowledge construction may become a new research perspective to build a teaching model based on the knowledge system. Based on the analysis of the connotation and teaching model of knowledge construction, this research creatively proposes a teaching model based on knowledge system construction and the "semi-finished product processing" strategy. There are three stages in the teaching model including before, during and after class. Collect practice data from personal knowledge acruisition, knowledge construction to knowledge integration, the model was applied in the course of "Multimedia Information Technology-Image Processing" relying on high school information technology teaching. By analyzing the data produced during teaching, it is found that this model can improve students' comprehensive applicable ability andlearning motivation. Finnally, according to suggestions of expert and interview on students, the model was revised and optimized to assure the rigorous and scientific.